Pengembangan Sistem Point of Sale berbasis Web (Studi Kasus: Bos Duren Malang) - Dalla Dirosa; Tri Astoto Kurniawan (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2021)
Bos Duren is a beverage shop in Malang that was founded in 2016. This shop sells several types of contemporary drinks with the main ingredients of durian fruit and coconut. The problem that occurs in Bos Duren Malang was that there are frequent human errors in recording transactions. Employees' errors can be seen from the low level of accuracy in calculating the number of sales and many sales transaction data recaps with different incoming money. The point of sale system was developed to solve these problems. Point of sale was expected to simplify the process of recording transactions. The waterfall model was used in the system development process. This research was conducted through a literature study, requirement engineering, design, implementation, testing, and decision-making. In this study, requirements engineering produced three actors, 37 functional requirements, and 1 non-functional requirement. This system has been tested using validation testing, integration testing, and unit testing. Testing on the system gets 100% valid for all tests. The test results show that the system was running and following the previous design and requirements engineering.